SOCIO-ECONOMIC STATUS AND PREVALENCE OF MALARIA IN SELECTED URBAN AND RURAL AREAS OF KOGI STATE, NIGERIA - USIO , UCHECHI TAIGA; ILEMONA , ADOFU; OKWUDILI , WALTER UGWUOKE (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
This study employed a descriptive survey research design with a quantitative approach to investigate the relationship between socioeconomic status and the prevalence of malaria in designated urban and rural areas of Kogi State, Nigeria. The research utilized a randomly selected population, employing questionnaires for data collection. Data analysis involved simple tabulation, percentages, frequency distribution, and binary logistic regression. The results indicated that higher education is associated with a decrease in malaria prevalence, suggesting the importance of educational initiatives. However, certain occupations, particularly farming, are linked to increased malaria risk, necessitating occupational health and safety measures. Additionally, higher income levels are associated with increased malaria prevalence, highlighting the need for policies addressing healthcare access for lower-income individuals. The study recommends promoting higher education, targeted awareness campaigns, occupational health measures for farmers, and policies improving healthcare access and income diversification to mitigate malaria prevalence in Kogi State, among others were proffered